PROMOTING HEARING HEALTH BEHAVIOR CHANGE IN ADULTS. (11th November 2018) - Frederick, M; Silverman, S; Laplante-Levesque, A; Nielsen, C; Saunders, G
Abstract: Uptake of hearing rehabilitation is impacted by a person's beliefs about hearing disability and hearing aids. Data show that interventions such as hearing aids result in positive outcomes, yet only about 25% of individuals with hearing impairment seek help for their hearing. To address this, we developed a brief photo-based intervention based on constructs from the Health Belief Model, the Transtheoretical Stages of Change Model and Self Determination Theory. The intervention is designed for use in any health-care setting in which a health-care provider can facilitate a conversation. It targets individuals who have not sought professional hearing evaluation despite perceiving hearing difficulties. One hundred one adults who perceived hearing difficulties but had not sought help were randomly assigned to either receive the intervention or not. Their help seeking behavior was followed up 6-months later. In the presentation we will describe the intervention and present findings from the study.